Utilizing Blood Clam and Green Mussel Shell-Derived CaO Biocoagulants for Acid Correction Testing in GCV Analysis - Triwardhani, Aline Bella; Fadlilah, Ilma; Dwityaningsih, Rosita (Jurnal Teknik Kimia dan Lingkungan, 2024)
Proper management of company-generated wastewater, specifically wastewater generated from acid correction testing in GCV analysis conducted by service providers and consulting firms, is crucial. Coagulation-flocculation emerges as an effective treatment method, utilizing biocoagulants derived from abundant blood clam and green mussel shells in Cilacap Regency. This study aims to identify the optimal calcination temperature for CaCO3 to CaO decomposition, assess the effectiveness of CaO biocoagulants in treating acid correction testing wastewater, and evaluate the impact of CaO biocoagulant dosage on pH, TDS, TSS, Turbidity, COD, and BOD5 parameters. Results indicate 1000°C as the best calcination temperature, with elemental compositions of Ca at 55.3% for blood clam shells and 58.7% for green mussel shells. The CaO coagulant's efficacy, derived from these shells, demonstrated significant pH increase (5 to 12.10), and substantial reductions in TDS (60%), TSS (79%), Turbidity (91%), BOD5 (93.71%), and COD (88%). The study reveals a dose-dependent relationship, with higher doses elevating pH and decreasing TSS, BOD5, and COD, while lower doses exhibit greater efficacy in reducing TDS and Turbidity values. This research underscores the potential of blood clam and green mussel shell-derived CaO biocoagulants in wastewater treatment, promoting environmental sustainability.